Application of Chemically Modified and Unmodified Waste Biological Sorbents in Treatment of Wastewater - John Kanayochukwu Nduka (International Journal of Chemical Engineering)
Protein wastes (feathers, goat hair) and cellulosic wastes (corn cob, coconut husks) were collected and washed with detergent solution, thoroughly rinsed and sun dried for 2 days before drying in an oven, and then ground. One-half of ground material was carbonized at a maximum temperature of 500°C after mixing with H2SO4. The carbonized parts were pulverized; both carbonized and uncarbonized sorbents were sieved into two particle sizes of 325 and 625 μm using mechanical sieve. Sorbents of a given particle size were packed into glass column.Then, textile wastewater that had its physicochemical parameters previously determined was eluted into each glass column and a contact time of 60 and 120 mins was allowed before analysis. Results showed 48.15–99.98 percentage reduction of NO3−, EC, Cl−, BOD, COD, DO, TSS, and TDS, 34.67–99.93 percentage reduction of NO3−, EC, Cl−, BOD, COD, DO, TSS, and TDS, 52.83–97.95 percentage reduction of Pb2+, Ni2+, Cr3+ and Mn2+ and 34.59–94.87 percentage reduction of Pb2+, Ni2+, Cr3+ and Mn2+. Carbonization, small particle, size and longer contact time enhanced the sorption capabilities of the sorbents. These show that protein and cellulosic wastes can be used to detoxify wastewater.